Jale Ghaemmaghmi: An Outstanding Social- Political Poet in Contemporary Persian - Zareifard, Raha; Rezaei, Mehdi (JOURNAL OF ADVANCES IN LINGUISTICS, 2018)
Jale Ghaemmaghmi is the late Ghajar and first Pahlavi poet who has social-political thought and is the outstanding poet among female poets. However, she is anonymous as the consequence of her limitation in her life. By studying her poems, it is found that her social-political thought is in line with some famous thinkers such as Dehkhoda, Bahar and Kasravi. She has more social poems in comparison to Forugh Farokhzad. This paper aims at investigating her thought by categorizing her poems to introduce the hidden layers of her thought to contemporary researchers in literature and sociology.